2019
DOI: 10.1002/leg3.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding fermented split yellow pea flour as a partial replacement of wheat flour in bread

Abstract: The effect of adding fermented split yellow pea flour (SYPF) as a partial replacement for wheat flour in bread was examined. Three sourdough culture levels (3%, 6.5%, and 10%) and two fermentation times (1 and 4 hr) were evaluated. Total titratable acidity of ferment was measured to determine acid development. Bread was baked using three ferment inclusion levels (25%, 35%, and 45%) for each of the six treatment combinations. Nonfermented control bread was baked for each inclusion and culture level by adding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Gandhi et al (2001) reported that the replacement of wheat flour at 40% level by defatted soy flour in the standard sweet biscuits yielded similar sensory scores when compared with that of 0% soya flour sample. Bourrer et al (2019) made bread with fermented split yellow pea flour (FSPF) with partial replacement of wheat flour and found that a higher percentage replacement affected the sensory quality of bread.…”
Section: Resultsmentioning
confidence: 99%
“…Gandhi et al (2001) reported that the replacement of wheat flour at 40% level by defatted soy flour in the standard sweet biscuits yielded similar sensory scores when compared with that of 0% soya flour sample. Bourrer et al (2019) made bread with fermented split yellow pea flour (FSPF) with partial replacement of wheat flour and found that a higher percentage replacement affected the sensory quality of bread.…”
Section: Resultsmentioning
confidence: 99%
“…All of the testing was completed when bread had been stored from 2 to 12 weeks. Thus, our objective to determine the effect of SYP flour on sensory properties will be valid for frozen bread samples as is also the case for other research studies (Bourré, Frohlich, et al., ; Bourré, McMillin, et al., ; Haglund et al., ; Zafar et al., ). Three batches (replications) of each of the four bread samples were made over two consecutive days.…”
Section: Methodsmentioning
confidence: 97%
“…In developing countries, there is growing research interest in fortifying wheat bread with processed legumes, especially fermented legume flour, to increase nutrient the intake of high‐quality protein and bioactive ingredients, and to take advantage of bread as a carrier of health‐promoting compounds (Shrivastava & Chakraborty, 2018). Though there are few reports on the inclusion of fermented legume flour in wheat‐based bread (Bourré et al., 2019; Hallén, Ibanoğlu, & Ainsworth, 2004; Kefalas et al., 2009; Rizzello, Calasso, Campanella, De Angelis, & Gobbetti, 2014; Shrivastava & Chakraborty, 2018), to the best of our knowledge, fermented African yam bean flour (FAYBF) as an ingredient in bread making has not been explored. Therefore, the objective of the study was to determine the effect of SSF on the functional properties, nutritional composition, and ANFs of AYB flour and to investigate the nutritional composition and the functional properties of the breads prepared from wheat‐FAYBF blends.…”
Section: Introductionmentioning
confidence: 99%